Comparación del agua y probiótico “EM.1” en el rendimiento del forraje verde hidropónico de maíz en Zúngaro Cocha 2023 - Torres Acosta, Miguel Alexis (2024)
The present study aims to evaluate the impact of water and the addition of probiotics on the yield of hydroponic green corn forage in Zúngarococha during the year 2023. To this end, experiments were carried out using a cross-sectional and prospective experimental design, allowing to compare the yield of the cultures with and without the application of probiotics. Statistical techniques such as Student's t-test for comparison of means and regression analysis were used to examine the relationship between the independent variables (water and addition of probiotics) and the dependent variable (forage yield). Data collection was carried out through detailed production records, precision weighing and storage of the information in Excel spreadsheets. In total, there were 98 observation units for hydroponic forage with and without the application of probiotics. The results showed that the addition of probiotics significantly improves forage yield, evidencing increases in both dry mass and other plant growth parameters, such as plant height, diameter and number of leaves. These findings suggest that the use of probiotics can be an effective strategy to optimize production in hydroponic systems, promoting more sustainable and efficient agriculture.